(untitled) (Revista científica Olimpia, 2020)
Bearing in mind the predominance of the Arterial Hypertension in Cuba, where more than two million 800 thousand adults at present endure Arterial Hypertension (HTA), specially the province of Cienfuegos, which reaches a valuation of 144,1 affected by every 1000 inhabitants, and the municipality of Palmira exists 4 970 affected persons, being the Popular Advice North Palmira one of those of major incidence with 22,86 affected ones, for every 1000 inhabitants; reoutfitter makes necessary the application of a Treatment to stabilize the arterial tension inside normal parameters in hypertense adults. The present work investigative takes as a purpose to determine the effect of a treatment reoutfitter by means of physical exercises and educational conferences on the arterial tension in hypertense adults of the above mentioned community. To come to the diagnosis, there was necessary the help of the doctor and the nurse, as well as the clinical information that turn out to be registered in the medical office. A study was realized in the period understood between September, 2016 and June, 2017, selecting a sample of 19 hypertense adults to whom measurements were applied to the beginning and end of the variables. Between both periods they were realized in the morning a plan of physical exercises with a frequency of three times for week and a duration of 45 minutes. The previous thing brought with it a control of the arterial tension, reducing the possible complications, diminishing the risks factors, raising this way the quality of life in the studied sample.